2016
DOI: 10.1002/mame.201600387
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Structured Electrospun Nanofibers for Improved Fog Harvesting Applications

Abstract: Collection of clean water from humid air has attracted immense attention in recent years due to the lack of access to pure drinking water among large section of population in several parts of the world. Hence, there is a persistent demand for the fabrication of robust, scalable membranes for efficient harvesting of pure water, especially in fog‐laden areas. Herein, three different membranes based on neat nanofibers, nanofibers with microparticles, and nanofibers with hierarchical structures (nanopillars) are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Recent study by Seo et al demonstrated that fog harvesting ability of a sample is defined by its wettability . Most studies focus on harvesting fog using hydrophobic or superhydrophobic surfaces . However, existence of water droplets on these hydrophobic surfaces in the Cassie impregnating state affects the transport step in water collection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study by Seo et al demonstrated that fog harvesting ability of a sample is defined by its wettability . Most studies focus on harvesting fog using hydrophobic or superhydrophobic surfaces . However, existence of water droplets on these hydrophobic surfaces in the Cassie impregnating state affects the transport step in water collection.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrate that the water collection efficiency can be improved by introducing secondary structures on the surface of the fibers. PVDF is chosen as a core material because of its high mechanical stability, hydrophobicity, and chemical resistant behavior . PNIPAM is chosen to form beads on the surface of PVDF fibers due to its inherent hydrophilic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Zwitterionic SBMA‐MPOSS‐PMMA solution was prepared by dissolving equal amount (6 wt %) of PMMA/SBMA with 5 wt % of MPOSS and 0.2 wt % of AIBN in HFIP. PMMA was added to improve the electrospinnability (spray to spin transition) of SBMA‐MPOSS mixture and also to enhance the formation of uniform and smooth nanofibers . The homogenous mixture was then purged with nitrogen for 15 min and subjected to concurrent electrospinning.…”
Section: Experimental Methodsmentioning
confidence: 99%
“… 7 , 16 20 One of the most promising techniques is electrospinning combining electrical poling and mechanical stretching to produce a high content of the β-phase in PVDF. This fabrication process is often used in scaffold production for tissue engineering, 21 , 22 energy harvesting, 23 filtration, 24 water collection, 25 production of hydrophobic materials, 26 , 27 and many more. During the electrospinning process, the electric field applied to polymer solution introduces electrical polarization.…”
Section: Introductionmentioning
confidence: 99%